eROSITA detection of a cloud obscuration event in the Seyfert AGN EC 04570–5206 - Markowitz, Alex; Krumpe, Mirko; Homan, David; Gromadzki, Mariusz; Schramm, Malte; Boller, Thomas; Krishnan, Saikruba; Saha, Tathagata; Wilms, Jörn; Gokus, Andrea; Hämmerich, Steven; Winkler, Hartmut; et al. (Astronomy & Astrophysics, 2024)
Context. Recent years have seen broad observational support for the presence of a clumpy component within the circumnuclear gas around supermassive black holes (SMBHs). In the X-ray band, individual clouds can manifest themselves when they transit the line of sight to the X-ray corona, temporarily obscuring the X-ray continuum and thereby indicating the characteristics and location of these clouds. Aims. X-ray flux monitoring with Spectrum Roentgen Gamma extended ROentgen Survey with an Imaging Telescope Array (SRG/eROSITA) has revealed that in the Seyfert 1 active galactic nucleus (AGN) EC 04570−5206, the soft X-ray flux dipped abruptly for about 10−18 months over 2020−2021, only to recover and then drop a second time by early 2022. Here, we investigate whether these flux dips and recoveries could be associated with cloud occultation events. Methods. We complemented the eROSITA scans with multiwavelength follow-up observations, including X-ray/UV observations with Swift, XMM-Newton, and NICER, along with ground-based optical photometric and spectroscopic observations to investigate the spectral and flux variability. Results. XMM-Newton spectra confirm that the soft X-ray flux dips were caused by partial-covering obscuration by two separate clouds. The 2020−2021 event was caused by a cloud with column density near 1 × 1022 cm−2 and a covering fraction of roughly 60%. The cloud in the 2022 event had a column density near 3 × 1023 cm−2 and a covering fraction near 80%. The optical/UV continuum flux varied minimally and the optical emission line spectra showed no variability in Balmer profiles or intensity. Conclusions. The transiting gas clouds are neutral or lowly-ionized, while the lower limits on their radial distances are commensurate with the dust sublimation zone (cloud 1) or the optical broad line region (cloud 2). One possible explanation is a dust-free, outflowing wind with embedded X-ray clumps. These events are the first cloud obscuration events detected in a Seyfert galaxy using eROSITA’s X-ray monitoring capabilities.
CRIS-Team Scopus Importer:2024-04-26
Keywords: galaxies: active; galaxies: Seyfert; X-rays: galaxies

Multi-wavelength study of Mrk 421 during a TeV flare - Gokus, Andrea; Kreikenbohm, A.; Leiter, K.; Bretz, T.; Dauser, Thomas; Dorner, D.; Elsaesser, D.; Eppel, F.; Heßdörfer, J.; Kadler, M.; Kraus, A.; Kreter, M.; et al. (Proceedings of Science, 2022)
The blazar Mrk 421 shows frequent, short flares in the TeV energy regime. Due to the fast nature of such episodes, we often fail to obtain sufficient simultaneous information about flux variations in several energy bands. To overcome this lack of multi-wavelength (MWL) coverage, especially for the pre- and post-flare periods, we have set up a monitoring program with the FACT telescope (TeV energies) and the Neil Gehrels Swift Observatory (X-rays). On 2019 June 9, Mrk 421 showed a TeV outburst reaching a flux level of more than two times the flux of the Crab Nebula at TeV energies. We acquired simultaneous data in the X-rays with additional observations by XMM-Newton and INTEGRAL. For the first time, we can study a TeV blazar in outburst taking advantage of highly sensitive X-ray data from XMM-Newton and INTEGRAL combined. Our dataset is complemented by pointed radio observations by Effelsberg at GHz frequencies. We present our first results, including the γ-ray and X-ray light curves, a timing analysis of the X-ray data obtained with XMM-Newton , as well as the radio spectra before, during and after the flare.
CRIS-Team Scopus Importer:2022-12-23

Statistical properties of flux variations in blazar light curves at GeV and TeV energies - Wagner, Sarah M.; Burd, P. R.; Dorner, D.; Mannheim, K.; Buson, S.; Gokus, Andrea; Madejski, G.; Scargle, J. D.; Arbet-Engels, A.; Baack, D.; Balbo, M.; Biederbeck, N.; et al. (Proceedings of Science, 2022)
Despite numerous detections of individual flares, the physical origin of the rapid variability observed from blazars remains uncertain. Using Bayesian blocks and the Eisenstein-Hut HOP algorithm, we characterize flux variations of high significance in the γ-ray light curves of two samples of blazars. Daily binned long-term light curves of TeV-bright blazars observed with the First G-APD Cherenkov Telescope (FACT) are compared to those of GeV-bright blazars observed with the Large Area Telescope on board the Fermi Gamma-ray Space Telescope (Fermi-LAT). We find no evidence for systematic asymmetry of the flux variations based on the derived rise and decay time scales. Additionally, we show that the daily-binned blazar light curves can be described by an exponential stochastic Ornstein-Uhlenbeck process with parameters depending on energy. Our analysis suggests that the flux variability in both samples is a superposition of faster fluctuations. This is, for instance, challenging to explain by shock-acceleration but expected for magnetic reconnection.
CRIS-Team Scopus Importer:2022-12-23

The first GeV flare of the radio-loud narrow-line Seyfert 1 galaxy PKS 2004-447 - Gokus, Andrea; Paliya, V. S.; Wagner, S. M.; Buson, S.; D'Ammando, F.; Edwards, P. G.; Kadler, M.; Meyer, M.; Ojha, R.; Stevens, J.; Wilms, Jörn (Astronomy & Astrophysics, 2021)
Context. On 2019 October 25, the Fermi-Large Area Telescope observed the first ever γ-ray flare from the radio-loud narrow-line Seyfert 1 galaxy PKS 2004-447 (z = 0.24). Prior to this discovery, only four sources of this type had shown a flare at gigaelectronvolt energies. Aims. We report on follow-up observations in the radio, optical-UV, and X-ray bands that were performed by ATCA, the Neil Gehrels Swift Observatory, XMM-Newton, and NuSTAR, respectively, and analyse these multi-wavelength data with a one-zone leptonic model in order to understand the physical mechanisms that were responsible for the flare. Methods. We study the source's variability across all energy bands and additionally produce γ-ray light curves with different time binnings to study the variability in γ-rays on short timescales during the flare. We examine the combined X-ray spectrum from 0.5 to 50 keV by describing the spectral shape with an absorbed power law. We analyse multi-wavelength datasets before, during, and after the flare and compare these with a low activity state of the source by modelling the respective spectral energy distributions (SEDs) with a one-zone synchrotron inverse Compton radiative model. Finally, we compare the variability and the SEDs to γ-ray flares previously observed from other γ-loud narrow-line Seyfert 1 galaxies. Results. At γ-ray energies (0.1-300 GeV) the flare reached a maximum flux of (1.3 ± 0.2) × 10-6 ph cm-2 s-1 in daily binning and a total maximum flux of (2.7 ± 0.6) × 10-6 ph cm-2 s-1 when a 3 h binning was used. With a photon index of Γ0.1-300 GeV = 2.42 ± 0.09 during the flare, this corresponds to an isotropic γ-ray luminosity of (2.9 ± 0.8) × 1047 erg s-1. The γ-ray, X-ray, and optical-UV light curves that cover the end of September to the middle of November show significant variability, and we find indications for flux-doubling times of ∼2.2 h at γ-ray energies. The soft X-ray excess, which is observed for most narrow-line Seyfert 1 galaxies, is not visible in this source. During the flare, the SED exhibits large Compton dominance. While the increase in the optical-UV range can be explained by enhanced synchrotron emission, the elevated γ-ray flux can be accounted for by an increase in the bulk Lorentz factor of the jet, similar to that observed for other flaring γ-ray blazars.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Galaxies: active; Galaxies: jets; Gamma rays: galaxies; Quasars: individual: PKS 2004-447